2014
DOI: 10.11648/j.ijmi.20140205.16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Multi-Detector Computed Tomography Angiography in the Evaluation of Lower Limb Ischemia

Abstract: Objective: To evaluate the value of MDCT Angiography in imaging the arterial tree of the lower limbs in peripheral vascular disease. Background: Peripheral arterial disease (PAD) is defined as any pathologic process causing obstruction to blood flow in the arteries, exclusive of the coronary and cerebral vascular beds. Conventional angiography is associated with 1-2% rate of complications and requires highly skilled physician to perform it. Non-invasive imaging modalities include duplex ultrasonography, magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…5,6 Noninvasive imaging modalities. 7 are Doppler ultrasonography, magnetic resonance angiography, MDCT angiography, and conventional arteriography. The gold standard of investigation in peripheral arterial disease is conventional arteriography, but it does not estimate the haemodynamic significance of obstructive lesions.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Noninvasive imaging modalities. 7 are Doppler ultrasonography, magnetic resonance angiography, MDCT angiography, and conventional arteriography. The gold standard of investigation in peripheral arterial disease is conventional arteriography, but it does not estimate the haemodynamic significance of obstructive lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 40 patients in this study, 30 (75%) patients were male and 10 (25%) were female (male to female ratio of 3:1). Similarly Kumar et al, 16 and Algazaar et al, 17 noted male predominance with male to female ratio of 6:1 and 1.5:1 respectively. However, Selvin 7 and Meijer et al, 18 found no gender differences in the prevalence of PAD.…”
Section: Discussionmentioning
confidence: 79%
“…19 Algazaar et al, similarly found smoking to be the most common risk factor (56.67%) followed by hypertension (50%) and diabetes (10%). 17 Cessation of smoking is associated with lower rates of amputation and longer survival in patients with PAD. 20 Hence cessation of smoking need to be encouraged to reduce the morbidity and mortality associated with PAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic atherosclerosis is a condition which progresses with age and decreases quality of life and life expectancy. Lower extremity peripheral arterial disease (PAD) is a common manifestation of systemic atherosclerosis in the elderly [1,2]. Peripheral arterial disease (PAD) is the most common condition affecting the arteries of the lower extremity.…”
Section: Introductionmentioning
confidence: 99%